Translation in Saccharomyces cerevisiae: initiation factor 4A-dependent cell-free system. - Blum, S (1989)
Yeast Saccharomyces cerevisiae genes TIF1 and TIF2 (translation initiation factor) encode a protein tentatively called translation initiation factor (Tif) due to the similarity of its amino acid sequence and its molecular weight to mammalian eukaryotic initiation factor 4A. To clarify whether Tif is involved in translation, we produced an affinity-purified anti-Tif antibody by using Tif isolated from a Tif-overproducing yeast strain as immunogen and an Escherichia coli strain expressing Tif from an expression vector to provide the extract for affinity purification of the antibody. By using chromatographic procedures and the affinity-purified anti-Tif antibody as probe to identify Tif-containing fractions, we purified Tif from wild-type yeast cells. When yeast cells containing the only TIF1 gene on a plasmid under the control of the galactose-inducible CYC1-GAL10 promoter were grown in medium containing glucose as the carbon source, the production of Tif was shut off and growth was arrested. Lysates made from these cells were inactive in in vitro translation. Addition of Tif to these lysates restored in vitro protein synthesis. These results show that Tif is a translation factor, the yeast homologue of mammalian translation initiation factor 4A.